2018
DOI: 10.1115/1.4040167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ramp Angle on the Anti-Loosening Ability of Wedge Self-Locking Nuts Under Vibration

Abstract: Recently, the wedge self-locking nut, a special anti-loosening product, is receiving more attention because of its excellent reliability in preventing loosening failure under vibration conditions. The key characteristic of a wedge self-locking nut is the special wedge ramp at the root of the thread. In this work, the effect of ramp angle on the anti-loosening ability of wedge self-locking nuts was studied systematically based on numerical simulations and experiments. Wedge self-locking nuts with nine ramp angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Spiralock thread form as an anti-loosening structure has a modified thread profile including a 30° wedge ramp, as shown in Fig. 24 [30]. After the Spiralock nut is tightened, the tip of the regular bolt will be embedded into the wedge ramp.…”
Section: Comparison With Spiralock Threadmentioning
confidence: 99%
See 2 more Smart Citations
“…Spiralock thread form as an anti-loosening structure has a modified thread profile including a 30° wedge ramp, as shown in Fig. 24 [30]. After the Spiralock nut is tightened, the tip of the regular bolt will be embedded into the wedge ramp.…”
Section: Comparison With Spiralock Threadmentioning
confidence: 99%
“…An FEM of engagement between regular bolt and Spiralock nut was built based on the method proposed by Liu et al [30], as shown in Fig. 25.…”
Section: Comparison With Spiralock Threadmentioning
confidence: 99%
See 1 more Smart Citation
“…In the vibration test, different vibration waveforms are used to simulate various conditions. Except for the sinusoidal vibration waveform, non-sinusoidal vibration waveforms are often required in the vibration technology (Liu et al, 2018; Nakata, 2012; Pagano et al, 2013). Thus, the vibration waveform is clearly a key consideration in the construction and control of a uniaxial electro-hydraulic shaking table.…”
Section: Introductionmentioning
confidence: 99%
“…15 The effect of the screw thread shape on the anti-loosening ability of wedge self-locking nuts was investigated by Liu et al, and the shape of the screw thread was described in the form of a ramp angle. 16 In addition to the shape and the topology, the contact pressure and its distribution are also sensitive to the interfacial hardness and the material stiffness of the contact parts. Benefiting from the development of the surface hardening techniques, such as laser peening and warm laser shock peening, variable hardness or material stiffness designs are receiving increasing attention in many aspects, especially in the application of resisting wear and damage of the contact interfaces with relative motion.…”
Section: Introductionmentioning
confidence: 99%